2017
DOI: 10.1175/jamc-d-16-0351.1
|View full text |Cite
|
Sign up to set email alerts
|

Wind-Blown Dust Modeling Using a Backward-Lagrangian Particle Dispersion Model

Abstract: Presented here is a new dust modeling framework that uses a backward-Lagrangian particle dispersion model coupled with a dust emission model, both driven by meteorological data from the Weather Research and Forecasting (WRF) Model. This new modeling framework was tested for the spring of 2010 at multiple sites across northern Utah. Initial model results for March–April 2010 showed that the model was able to replicate the 27–28 April 2010 dust event; however, it was unable to reproduce a significant wind-blown … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 57 publications
1
20
0
Order By: Relevance
“…Overall, the WRF-STILT dust modeling framework was able to capture the timing and duration of the dust event ( figure 2(a)). Modeled dust emissions in figure 2(b) indicated that the Great Salt Lake Desert (GSLD), exposed portions of the GSL lake bed, Delta, and Lake Sevier were the largest emitters of dust during this event, which is consistent with results from previous work (Hahnenberger and Nicoll 2012, Steenburgh et al 2012, Mallia et al 2017. The majority of dust contributions towards ASP, according to WRF-STILT, indicated that the GSLD was the biggest contributor of dust (46%), followed by Lake Sevier (21%), Delta (13%), and other source regions across the eastern Great Basin (11%) ( figure 2(c)).…”
Section: Dust Emission and Transportsupporting
confidence: 88%
See 3 more Smart Citations
“…Overall, the WRF-STILT dust modeling framework was able to capture the timing and duration of the dust event ( figure 2(a)). Modeled dust emissions in figure 2(b) indicated that the Great Salt Lake Desert (GSLD), exposed portions of the GSL lake bed, Delta, and Lake Sevier were the largest emitters of dust during this event, which is consistent with results from previous work (Hahnenberger and Nicoll 2012, Steenburgh et al 2012, Mallia et al 2017. The majority of dust contributions towards ASP, according to WRF-STILT, indicated that the GSLD was the biggest contributor of dust (46%), followed by Lake Sevier (21%), Delta (13%), and other source regions across the eastern Great Basin (11%) ( figure 2(c)).…”
Section: Dust Emission and Transportsupporting
confidence: 88%
“…In an effort to quantify the impacts of wind-blown dust events along the Wasatch Front for the mid-April dust event, we used a backward Lagrangian modeling framework that was recently developed specifically for dust simulations (Mallia et al 2017). This model was able to successfully capture the timing and magnitude of two major dust events across northern Utah during the spring of 2010, when compared to a number of air quality stations along the Wasatch Front.…”
Section: Aerosol Modelingmentioning
confidence: 99%
See 2 more Smart Citations
“…All components are first given as hourly standard error (2 nd column) and, if applicable, correlation is applied between same-day observations using a decay time-scale parameter (3 rd column). Component errors are then aggregated to express observational error in enhancements that represent an average for a given afternoon (4 th column error components are not expected to be random within a given afternoon), while R transWIND is given decaying correlation with increasing time between observations, assuming a correlation timescale of 2.8 hours as in Mallia et al (2017). In this study we assume error to be constant across sites, and do not account for spatial correlation of measurements between sites; however, it should be noted that in a real-data application, errors are likely to be correlated between towers, especially if separation distances between sites are small (as they are in this study area).…”
Section: Error Covariance Parametersmentioning
confidence: 99%